Biofouling in heat exchangers - Melo, Luís Manuel Ferreira (1992)
Heat exchangers are used to transfer heat from a hot fluid to a cold fluid. In general, the two fluids flow through appropriate channels (tubes, spaces between parallel plates or between tubes) within the equipment. Solid surfaces made of metal or, less often, of some polymer (teflon, e.g.) separate the fluids.